(untitled) (Agro Productividad, 2025)
Objective: To identify the growth of Brachiaria decumbens by biofertilizing the seed with Rhizophagus intraradices and/or Azospirillum brasilense in combination with exogenous applications of brassinosteroids Design/methodology/approach: In this study, nursery research combining biofertilization of B. decumbens with R. intraradices and/or A. brasilense in combination with exogenous brassinosteroid applications, was carried out to study their effects on plant growth. Results: The results indicate an increase in morphological and physiological components of B. decumbens with Hbr applications alone and/or in combination with R. intraradices. Mycorrhizal colonization favoured and increased N and P content with Hbr applications. Limitations on study/implications: Dry matter allocation may change if B. decumbens is biofertilized with other biofertilizer collections. Findings/conclusions: We conclude that Hbr not only favoured growth, but also colonization with R. intraradices and consequently biomass production, and N and P content in plant tissue. The growth response and nutrient exchange suggest interdependence between brassinosteroids and the endomycorrhizal fungus.